HEMATOLOGICAL PARAMETERS IN THE ASSESSMENT OF PREGNANCY INDUCED HYPERTENSION - DIPTI MOHAPATRA; NIBEDITA PRIYADARSINI; MANASI BEHERA; PRIYAMBADA PANDA; TAPASWINI MISHRA (International Journal of Pharma and Bio Sciences, 2015)
Pregnancy induced hypertension (PIH) is one of the most common causes of both maternal and neonatal morbidity. The hypertensive disorders account for thrombocytopenia in pregnancy and the risk of anemia may also increase with the severity of hypertensive disorders. Hyperuricemia in hypertensive pregnancy is an important finding because it identifies women at increased risk of adverse fetal outcome even women with gestational hypertension without any other features of pre-eclampsia. There is a constant ongoing research on hematological parameters for better predictors and prognostic factors to assess the progress and severity of the disease. The present study was undertaken to evaluate hematological parameters in assessment of pregnancy induced hypertension.